The Integration of Technology in English Language Teaching to Stimulate Students’ Critical Thinking (Universitas Negeri Semarang, 2023)
This study was aimed at describing the effectiveness of integrating technology in English language teaching for stimulating students’ critical thinking designing in the form of a systematic literature review. The data were obtained by documenting relevant research articles published in national and international journals indexed in SINTA (4-1) and SCOPUS. There were 52 research articles focusing on the integration of technology in English language teaching for stimulating students’ critical thinking. Those research articles were re-selected by using inclusion criteria. The gained data were reviewed, compared, and interpreted with relevant theories. A factual content analysis was conducted to check its validity and reliability. The findings showed that the integration of technology is distributed into three learning aspects; learning method, learning media, and learning platform. Technology is integrated as a learning method through the implementation of online learning, digital storytelling, and online peer-reviewed assessment. Those methods showed a positive impact towards students’ critical thinking. The integration of technology as a learning media was purposed to provide a fun learning environment and improve students’ learning motivation. It also influences students’ critical thinking. It was found that the learning media used by teachers in English language teaching were Youtube video, Toondoo, E-book, Mind Mapple, podcast, and other browsing applications. Those media were effective in stimulating students’ critical thinking. Using technology as a learning platform is also effective to stimulate students’ critical thinking as a supporting tool in providing forum discussions and conducting online classrooms interaction that enable students to explore their critical thinking skills.